1994
DOI: 10.1007/bf00316283
|View full text |Cite
|
Sign up to set email alerts
|

Spinal bone mass after long-term treatment with L-Thyroxine in postmenopausal women with thyroid cancer and chronic lymphocytic thyroiditis

Abstract: This study investigated the effect of long-term treatment upon bone density with L-Thyroxine in postmenopausal women compared with untreated postmenopausal women with climacteric symptoms. We measured spinal bone density in three groups (n = 84) of postmenopausal women: (A) those treated with TSH-suppressive doses of L-Thyroxine for a medium of 5 years after removal of thyroid cancer; (B) those on L-Thyroxine treatment for a median of 9 years after being diagnosed with chronic lymphocytic thyroiditis (CLT); an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 19 publications
1
34
1
Order By: Relevance
“…Previous studies have reported conflicting results, bone loss being described as minimal [18,19], significant [8,11,12,[20][21][22][23] or absent [9,10,24]. The same is valid for the preferential localization of the bone loss, mainly lumbar [20,23,25], femoral [11,21] or appendicular [8], and also for the influence of menopause [9,11,26].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies have reported conflicting results, bone loss being described as minimal [18,19], significant [8,11,12,[20][21][22][23] or absent [9,10,24]. The same is valid for the preferential localization of the bone loss, mainly lumbar [20,23,25], femoral [11,21] or appendicular [8], and also for the influence of menopause [9,11,26].…”
Section: Discussionmentioning
confidence: 68%
“…Nevertheless, the effect of prolonged subclinical hyperthyroidism on bone mass is controversial [5][6][7]. Cross-sectional studies of bone density in patients on levothyroxine (LT 4 ) suppressive therapy yielded discordant results ranging from unchanged bone mass [8][9][10] to 20-23% reductions in axial and appendicular bone mass [11,12]. Confounding variables such as parathyroid and menopausal status, and also prior history of hyperthyroidism, may be responsible for such differences.…”
Section: Introductionmentioning
confidence: 93%
“…With respect to hyperthyroidism due to suppressive LT4 treatment, some trials included premenopausal women with little or no change in BMD between controls and long-term treated patients (Franklyn et al 1992, Giannini et al 1994, Marcocci et al 1994, Muller et al 1995. Studies performed in postmenopausal women showed decreased BMD in all measured sites in two trials (Diamon et al 1991, Kung & Yeung 1996 and no changes in another six (Franklyn et al 1992, Giannini , Hawkins et al 1994, Marcocci et al 1994, Muller et al 1995, Go¨rres et al 1996, Guo et al 1997.…”
Section: Discussionmentioning
confidence: 96%
“…Some reports, including a meta-analysis by Wü ster (9), have suggested that the bone mineral density (BMD) is reduced in patients taking long-term treatment to suppress thyroid stimulating hormone (TSH) (levothyroxine, L-T 4 ) compared with controls (10-13). However, other studies have failed to confirm this decremental effect of L-T 4 treatment on BMD (14)(15)(16)(17) or on the prevalence of fracture (18,19). L-T 4 treatment that does not suppress TSH seems to have little effect on bone (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%